A Baseline for the Blue Economy: Catch and Effort History in the Republic of Seychelles’ Domestic Fisheries - Christ, Hanna J.; White, Rachel; Hood, Lincoln; Vianna, Gabriel M. S.; Zeller, Dirk (Frontiers in Marine Science, 2020)
The adoption of sovereign blue bonds by the Republic of Seychelles, hereafter referred to as Seychelles, focuses on resource sustainability and illustrates options for island countries to use their ocean resources for years into the future. The fishing industry is one of the main pillars of Seychelles’ economy and is of crucial importance for domestic food- and employment-security. In order to promote long-term ecological sustainability and economic viability of domestic fisheries, accurate and long-term baseline information is required. Such baseline data were derived here with a reconstruction of the Seychelles’ domestic fisheries catches and fishing effort within its Exclusive Economic Zone (EEZ) from 1950 to 2017, coupled with resulting Catch Per Unit Effort data (CPUE). The total reconstructed domestic catch was approximately 1.5 times larger than the baseline as reported by the United Nations Food and Agriculture Organization (FAO) on behalf of Seychelles from 1950 to 2017 after adjustment for fully domestic catches within the EEZ. Domestic catches (i.e., excluding the large-scale industrial pelagic catches) increased by over 500% throughout the time period, growing from 1,900 t⋅year−1 in the 1950s to around 11,200 t in 2017. The major targeted taxa were jacks (Carangidae), tuna-like fishes (Scombridae) and snappers (Lutjanidae). Total fishing effort in the form of fishing capacity grew from 21,500 kWdays in 1950 to over 3.4 million kWdays in 2017. The resultant artisanal CPUE displayed a declining trend over time, suggesting a potential decline in relative abundance of fish populations within the Seychelles EEZ or targeted fishing areas.